Analyses of ecosystem productivity using field measurement and remote sensing, and microalgae diversity at Mayangan and Sendang Biru Beaches, East Java, Indonesia - UMI ZAKIYAH; ALIVIA SALSABILA KUSUMA TANYA SANTOSO; ZULKISAM PRAMUDIA; TIA DWI IRAWANDANI; DISTA ERINTIKA (Society for Indonesian Biodiversity, 2025)
Abstract. Zakiyah U, Santoso ASKT, Pramudia Z, Irawandani TD, Erintika D. 2025. Analyses of ecosystem productivity using field measurement and remote sensing, and microalgae diversity at Mayangan and Sendang Biru Beaches, East Java, Indonesia. Biodiversitas 26: 1777-1788. This study evaluates ecosystem productivity and microalgae biodiversity at Mayangan Beach and Sendang Biru Beach, East Java, Indonesia using chlorophyll-a as an indicator, as it functions as an active metabolic component in the photosynthesis process of microalgae, the primary producers in aquatic ecosystems. By integrating in-situ measurements and remote sensing via Sentinel-2 Imagery, the study assesses water quality, microalgae composition, and biodiversity indices, which mutually influence trophic balance and food chain efficiency. The abundance of microalgae reflects nutrient availability and environmental conditions, determining primary productivity and aquatic ecosystem health. Results indicate that Mayangan Beach exhibits higher chlorophyll-a concentrations due to nutrient-rich runoff, while Sendang Biru Beach maintains more stable but oligotrophic conditions. Chlorophyll-a, as a primary photosynthetic pigment, is essential for analyzing ecosystem productivity as it directly correlates with microalgae abundance. Bacillariophyta is the dominant microalgae group in both waters, highlighting its ecological role in aquatic productivity. These findings underscore the importance of integrating remote sensing with field data for effective coastal monitoring. Additionally, the study emphasizes how environmental factors such as nutrient input and hydrodynamics influence ecosystem productivity. The results provide insights for sustainable coastal management and demonstrate the potential of remote sensing technology in assessing marine ecosystem health.